The Natural Flavone Acacetin Confers Cardiomyocyte Protection Against Hypoxia/Reoxygenation Injury via AMPK-Mediated Activation of Nrf2 Signaling Pathway - Wu, Wei-Yin; Li, Yun-Da; Cui, Yu-Kai; Wu, Chan; Hong, Yi-Xiang; Li, Gang; Wu, Yao; Jie, Ling-Jun; Wang, Yan; Li, Gui-Rong (Frontiers in Pharmacology, 2018)
The present study investigates the potential signal pathway of acacetin in cardioprotection against ischemia/reperfusion injury using an in vitro hypoxia/reoxygenation model in primary cultured neonatal rat cardiomyocytes and H9C2 cardiomyoblasts. It was found that acacetin (0.3-3 uM) significantly decreased the apoptosis and ROS production induced by hypoxia/reoxygenation injury in cardiomyocytes and H9C2 cardiomyoblasts via reducing the pro-apoptotic proteins Bax and cleaved-caspase-3 and increasing the anti-apoptotic protein Bcl-2. In addition, acacetin not only suppressed the release of pro-inflammatory cytokines TLR-4 and IL-6 induced by hypoxia/reoxygenation injury, but also increased the secretion of anti-inflammatory cytokine IL-10. Moreover, acacetin increased Nrf2 and HO-1 in a concentration-dependent manner, and rescued SOD1 and SOD2 reduction induced by hypoxia/reoxygenation insult. These beneficial effects of acacetin disappeared in cells with silenced Nrf2, suggesting that Nrf2 activation participates in the cardioprotective effect of acacetin against hypoxia/reoxygenation insult. However, acacetin-induced Nrf2 activation was not observed in cells with silenced AMPK and in ventricular tissues of rat hearts treated with the AMPK inhibitor Compound C and subjected to ischemia/reperfusion injury. Our results demonstrate for the first time that AMPK-mediated Nrf2 activation is involved in the cardiomyocytes protection of acacetin against hypoxia/reoxygenation injury by activating a series of intracellular signals involved in anti-oxidation, anti-inflammation, and anti-apoptosis.